Personal and contextual determinants of elite young athletes' persistence or dropping out over time - Le Bars, H.; Gernigon, C.; Ninot, G. (Scandinavian Journal of Medicine & Science in Sports, 2009)
Two studies were conducted among elite young judokas to examine (a) whether those who persisted in national training centers (n=52) were different from dropouts (n=52) in their perceptions of coach-, parent-, and peer-induced motivational climates, goal orientations, self-perceptions, perceived competence, and intention of dropping out, and (b) whether these variables varied during the persisting athletes' (n=82) first 2 years in these centers. Compared with persisting athletes, dropouts perceived the roles of coaches, parents, and peers as less task-involving, were less task-oriented, and intended more to drop. The association of peer-, coach-, and parent-induced task-involving climates predicted athletes' persistence. During the 2 years, persisting athletes' perceptions of coach-, parent-, and peer-induced task-involving climates decreased, while perceptions of a coach-induced ego-involving climate and the intention of dropping out increased in spite of more positive self-perceptions. Gender differences favoring males were observed for self-perceptions only. These results stress the importance for all the agents of the athletes' social environment to promote task-involving climates, because such climates appear to be naturally prone to degradation in the context of elite competition. The results also shed light on some high-level athletes' characteristics regarding motivational dispositions and self-concept.